Effect of leaves extract of Adhatoda vasicia plant against some wounds contamining bacteria by using sensitive test (Baghdad Science Journal, 2007)
This study has been done on plant [Adhatoda vasicia , Acanthaceae family],which has been collected from gardens of university of Baghdad The leaves of plant were extracted by methanol alcohol obtain the crude extraction good ratio(30%).Eighty swabs or samples were collected from several wounds patients of hospitals in Baghdad city.These swabs were cultured on blood and MacConkey ager to isolate bacteria and identified by appearance and bio chemical tests.The results showed that(60)somples were positive(75%)for tests bacteria white the other(20)swabs were negative(25%).The bacteria were identified as Pseudomonas aeruginosa ,Staphylococcus awreus , Esherichia coli,Proteus spp and Klebsiella spp; and their number percentage were(32)isolates(49.2%),(7)isolates(10.7%),(5)isolates(7.6%),(1)isolate(1.5%)and(20)isolates(30.7%)respectivity.Crude extract teated by sensitivity test against the bacteria with concentration (2,4,6,8,10,12mg/ml).The results showed that the inhibition zone increased with increasing ils concentration The best concentration that inhited most of the bacteria is(6 mg/ml) of the crud extract that was isolated from wounds .